ADAM'S BRIDGE - Chatterjee, Arup K. ([S.l.])
1 online resource
Keywords: Adam's Bridge offers the first comprehensive transdisciplinary study of the famous eponymous tombolo (also known as Ram Setu) combining its sacral, historical, geological, political, performative, and heritage aspects into one framework, viewed under the critical lenses of island studies and cultural theory. The book elucidates the entanglement of Adam's Bridge's discursive history with India's colonial history, contemporary geology, domestic politics, and the nation's emerging position in a complex geopolitical order in and around the Indian Ocean region, vis--vis increasing Sino-American involvement in Indo-Sri Lankan relations. Without foregrounding any absolute scientific claims on the location of the sandbars that inspired sage Valmiki's Ram Setu and the Ramayan legacy or hindering narratives of religious faiths and folklore revolving around the structure, this intellectual historiography traces the parallel evolution of traditions of compassionate questioning and devotion for Indic sacred beliefs among commentators across the millennia from both Indian and non-Indian spectra, seen in juxtaposition with the biotic and abiotic diversity of the Gulf of Mannar and Palk Bay. Looking beyond secular-versus-religious debates, this book will be of interest to scholars of ocean and island studies, coastal economies, archipelagic geographies, environmental history, heritage studies, colonial studies, and cultural theory. Adam's Bridge unifies a consortium of themes, ranging across ecological and livelihood sustainability, environmentalism, soteriology, economic and geostrategic history, and the United Nations Convention on the Law of the Sea, in conceptualizing a compellingly nuanced chronicle for India's enchanted bridge.'